Spleen-Dependent Immune Protection Elicited by CpG Adjuvanted Reticulocyte-Derived Exosomes from Malaria Infection Is Associated with Changes in T cell Subsets' Distribution - Martín-Jaular, Lorena; de Menezes-Neto, Armando; Monguió-Tortajada, Marta; Elizalde-Torrent, Aleix; Díaz-Varela, Míriam; Fernández-Becerra, Carmen; Borras, Francesc E.; Montoya, Maria; del Portillo, Hernando A. (Frontiers in Cell and Developmental Biology, 2016)
Reticulocyte-derived exosomes (rex) are 30-100 nm membrane vesicles of endocytic origin released during the maturation of reticulocytes to erythrocytes upon fusion of multivesicular bodies with the plasma membrane. Combination of CpG-ODN with rex obtained from BALB/c mice infected with the reticulocyte-prone non-lethal P. yoelii 17X malaria strain (rexPy), had been shown to induce survival and long lasting protection. Here, we show that splenectomized mice are not protected upon rexPy+CpG inmunizations and that protection is restored upon passive transfer of splenocytes obtained from animals immunized with rexPy+CpG. Notably, rexPy immunization of mice induced PD1- memory T cell expansion with effector phenotype. Proteomics analysis of rexPy confirmed their reticulocyte origin and demonstrated the presence of parasite antigens. Our studies thus prove, for what we believe is the first time, that rex from reticulocyte-prone malarial infections are able to induce splenic long-lasting memory responses. To try extrapolating these data to human infections, in vitro experiments with spleen cells of human transplantation donors were performed. Plasma-derived exosomes from vivax malaria patients (exPv) were actively uptaken by human splenocytes and stimulated spleen cells leading to expansion of T-cells.